The Effect of Financial Literacy and Social Proof on Impulse Purchases of Virtual Items among Generation Z - Juan Wody Romansa; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
This study analyzes the influence of Financial Literacy and Social Proof on Impulsive Buying behavior of virtual items among Generation Z users on the Roblox platform, with Usage Intensity as a mediating variable. Employing a quantitative approach, data were collected from 105 active Gen Z Roblox users in Indonesia through purposive sampling and analyzed using Structural Equation Modeling (PLS-SEM). The results reveal a unique phenomenon where Financial Literacy and Social Proof do not directly trigger impulsive buying. Instead, both variables significantly increase Usage Intensity. Subsequently, Usage Intensity acts as a full mediator that effectively bridges the influence of cognitive and social factors on impulsive buying decisions. These findings confirm a financial literacy paradox in the virtual economy, where high engagement and screen time (Usage Intensity) effectively weaken rational control, bridging the gap between cognitive knowledge and impulsive purchasing decisions.